DOES CONSIDERATION OF FUTURE CONSEQUENCES MODERATOR THE RELATIONSHIP BETWEEN ROLE STRESSORS AND CYBERLOAFING: A CONCEPTUAL PAPER - Mohammad Said Ibrahim Al-Shuaibi; Chandrakantan Subramaniam; Faridahwati Mohd. Shamsudin (Scholar Express Journals, 2021)
With the advent of the technology and its spread at the workplace at the end of the 20t century and the beginning of the 21st century, the concerns elevated among employers and managers on how employees using this technology at the workplace. Employers are striving to find ways to control and direct these technologies to be beneficial rather than being distraction tools to the employees. The use of the internet for non-work-related activities at the workplace known as cyberloafing. This paper provide aims to explore the different effect of stressors and hindrances on cyberloafing from the perspective of conservation resources of theory. Therefore, this paper reviewed the previous scholarly work in order to propose a framework and state propositions that can be empirically applied in the future. In addition, the current study add to the body of knowledge by incorporating individual future orientation to the framework as expected moderator.
Keywords: Cyberloafing; role overload; role ambiguity; role conflict